Answer:
[tex]\displaystyle b = -22[/tex]
Step-by-step explanation:
We are given the function:
[tex]\displaystyle f(x) = (x^3+bx+6)(g(x))[/tex]
Where b is a constant and g is a differentiable function.
And we want to determine the value of b such that f'(2) = 0.
Find f' using the product rule:
[tex]\displaystyle \begin{aligned} f'(x) & = \frac{d}{dx}\left[ (x^3+bx+6)(g(x))\right] \\ \\ & = \frac{d}{dx}\left[ x^3 + bx + 6\right] g(x) + (x^3+bx+6)\frac{d}{dx}\left[ g(x)\right] \\ \\ & = (3x^2+b)(g(x)) + (x^3 + bx + 6)(g'(x))\end{aligned}[/tex]
Substitute using known values and solve for b:
[tex]\displaystyle \begin{aligned}f'(2) = 0 & = (3(2)^2+b)(g(2)) + ((2)^3+b(2)+6)(g'(2)) \\ \\ 0 & = (12+b)(3) + (14+2b)(-1) \\ \\ 0 & = 22 +b \\ \\ b & = -22\end{aligned}[/tex]
In conclusion, the value of b is -22.